Situation Report: Romania, 4 August 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Greek Foreign Minister Visits Romania Ceausescu Receives Iraqi Military Delegation Second Canadian-Made Nuclear Reactor Sold to Romania A New Look at Scientific and Thermal Power Production Romanian Has a New Catholic Bishop Four-Year Program for Romanian Literature Announced The World Student Games - the Universiada [Universiade] '81- in Bucharest